ENTREPRENEUR SEBAGAI PILIHAN KARIR MAHASISWI MALUKU UTARA: PERAN EFIKASI DIRI DAN KEPRIBADIAN - Muhammad Rachmat (Asian Journal of Innovation and Entrepreneurship, 2012)
Entrepreneurial research among female undergraduate students has become more important these days. This study is to investigate the role of self-efficacy and personality dimension (openness to experience) based on Theory of Planned Behavior. Survey conducted to 7 female students of Maluku Utara. Hypotheses tested using Partial Least Square. The result showed that subjective norm has the stronger relationship with entrepreneur as a career for female undergraduate students. Interestingly, self-efficacy was not significant determinant of entrepreneurial intentions in this study, contrary to earlier studies. Keywords: Entrepreneurial Intention, Self-Efficacy, Personality, Female Undergraduate Students, Maluku Utara